Population genetics and microevolutionary theory - Templeton, Alan Robert (Hoboken, New Jersey : Wiley-Blackwell, 2021)
'Population genetics is concerned with the origin, amount, and distribution of genetic variation present in populations of organisms, and the fate of this variation through space and time. This variation constitutes the fundamental basis of evolutionary change - in its most basic sense, evolution is the genetic transformation of reproducing populations over space and time. Population genetics is therefore at the very heart of evolutionary biology, and can be thought of as the science of the mechanisms responsible for microevolution, or evolution within species.'--
Includes bibliographical references and index.
Keywords: Population genetics; Evolution (Biology).